A dataset of textile fibres transferred between garments in a simulated assault for forensic interpretation and statistical analysisUTS Research Data PortalUTS Research Data Portal - Victoria Lau; Xanthe Spindler; Claude Roux (Data in Brief)
The data presented corresponds to the paper “The transfer of fibres between garments in a choreographed assault scenario” [1]. The dataset describes the features (generic fibre type, colour, length, recovered location) of 26101 fibres transferred and recovered following choreographed assault simulations performed by participants wearing a cotton T-shirt and polyester/cotton hoody. This data has been made available so others may employ different statistical methods and modelling approaches to further investigate relationships amongst variables, including continuous length of transferred target and extraneous fibres. Furthermore, forensic practitioners and researchers may use this data for training, teaching and in the evaluation of forensic fibre findings.